(untitled) (Global Journal of Human-Social Science, 2018)
In the last decades most of the parents turned their attention towards teaching their children private lessons especially in scientific fields thinking that public education is no longer beneficial for them In the light of this tight the current research aims to shed light on the reasons that drive pupils to prefer private tutoring rather than public education In other words it endeavours to test the attitudes of the tutees and their performance in comparison to other pupils To this vein data were collected quantitatively and qualitatively by means of a questionnaire an interview and a classroom observation The sample of the study was selected randomly from the three levels at Mohamed Belkheir secondary school in Saida To this end the findings demonstrated that most of the tutees displace positive attitudes towards private education The results also revealed that the central factor revolves around overcrowded classrooms and the poor level of teaching